The Importance of Using Interactive Methods in Improving Students' Historical Analysis and Independent Thinking Skills in the Educational Process - Amonov Davronjon Sheralievich (Genius Journals, 2022)
There is talk about educating young people as initiative people, getting them used to nonstandard thinking, achieving high results in a short time without spending excessive mental and physical effort.
Keywords: National pedagogy; striving for spirituality; development of strength; endurance